Crosstalk between cancer stem cells and the tumor microenvironment drives progression of premalignant oral epithelium - Peter J. Polverini; Felipe Nör; Jacques E. Nör (Frontiers Media S.A., 2023)
Cancer stem cells (CSC) are a subpopulation of cancer cells that exhibit properties of self-renewal and differentiation and have been implicated in metastasis and treatment failures. There is mounting evidence that carcinogen-initiated mucosal epithelial stem cells acquire the CSC phenotype following exposure to environmental or infectious mutagens and are responsible for promoting the malignant transformation of premalignant (dysplastic) epithelium. CSC further contribute to the progression of dysplasia by activating signaling pathways through crosstalk with various cell populations in the tumor microenvironment. Two cell types, tumor-associated macrophages (TAM) and vascular endothelial cells (EC) nurture CSC development, support CSC stemness, and contribute to tumor progression. Despite mounting evidence implicating CSC in the initiation and progression of dysplastic oral epithelium to squamous cell carcinoma (SCC), the molecular mechanisms underlying these synergistic biological processes remain unclear. This review will examine the mechanisms that underlie the transformation of normal epithelial stem cells into CSC and the mechanistic link between CSC, TAM, and EC in the growth and the malignant conversation of dysplastic oral epithelium.